Sensing the Nation's Law Historical Inquiries into the Aesthetics of Democratic Legitimacy - Huygebaert, Stefan; Condello, Angela; Marusek, Sarah; Antaki, Mark (Studies in the History of Law and Justice, 2018)
X, 284 p. 52 illus.